Study of the Austenitization Process in a P91 Steel - Signorelli, Gisella Fernanda; Danón, Claudio Ariel; Luppo, María Inés (International Atomic Energy Agency; Austria, 2018)
Fil: Signorelli, Gisella Fernanda Comisión Nacional de Energía Atómica; Argentina